1993
DOI: 10.1063/1.108514
|View full text |Cite
|
Sign up to set email alerts
|

Deposition of polytetrafluoroethylene films by laser ablation

Abstract: Films of polytetrafluoroethylene (PTFE) were deposited by laser ablation using the fourth harmonic, at 266 nm, of a Nd-YAG laser. The films are found to be stoichiometric with the correct optical properties. We suggest that UV absorption onsets the pyrolitic decomposition of PTFE leading to a monomer that subsequently repolymerizes onto a substrate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
36
0

Year Published

1994
1994
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 106 publications
(38 citation statements)
references
References 20 publications
2
36
0
Order By: Relevance
“…We concluded that the heterogephotoablation. 2 In other cases, photodegradation is a serious drawback that has often limited wideneous nature of PTFE (i.e., coexistence of crystalline and amorphous phases), is a determining facspread use of this polymer.…”
Section: Introductionmentioning
confidence: 99%
“…We concluded that the heterogephotoablation. 2 In other cases, photodegradation is a serious drawback that has often limited wideneous nature of PTFE (i.e., coexistence of crystalline and amorphous phases), is a determining facspread use of this polymer.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, previous reports have described the successful use of the absorbed radiation to photothermally depolymerize the target material, with subsequent repolymerization at the substrate. 11,12,31 However, when the degree of re-polymerization was incomplete, as when a photochemical reaction caused the loss of a pendant functional group, the polymer was subjected to substantial structural modification in comparison with the bulk native material.…”
Section: Ultraviolet (Uv) Pld and Maplementioning
confidence: 99%
“…[32][33][34] Although the deposition of almost intact polymers is possible near the ablation threshold fluence, the process is complicated by molecular structures that cannot be subjected to the same bond-breaking and repolymerization scheme used for addition polymers. 11,12,31 Previous reports have described the use of a KrF excimer laser (248 nm) to deposit amorphous copper phthalocyanine (CuPc), aluminum tris-8-hydroxyquinline (Alq 3 ) and 4-dialkylamino-4 -nitrostilbensen (DANS), 32,33 and of a Nd:YAG laser (355 nm) for poly(p-phenylene vinylene) (PPV) films. 34 Although these films were electroluminescent, their efficiencies were not comparable to those of spin-coated or sublimated control materials as a result of losing molecular structure fidelity in the ablative transfer from target to substrate.…”
Section: Ultraviolet (Uv) Pld and Maplementioning
confidence: 99%
“…7 It is also a very promising tool for polymer-film synthesis. [8][9][10][11][12][13] Although many groups have reported on the synthesis of materials by photo-reaction induced by infrared lasers, [14][15][16][17][18] those induced by excimer lasers are relatively few. [19][20][21][22][23][24][25] In the present paper, we report on synthesis of silicon-based polymer films by excimer laser-induced photoreaction of phenylsilane and methylphenylsilane.…”
Section: Introductionmentioning
confidence: 99%